Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20071697
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic miR-143 Inhibits Growth of HER2-Positive Gastric Cancer Cells by Suppressing KRAS Networks Including DDX6 RNA Helicase

Abstract: Gastric cancer (GC) is one of the most common cancers worldwide. In the clinical setting, the identification of HER2 overexpression in GC was a significant finding, as trastuzumab, an anti-HER2 drug, provides a survival advantage to HER2-positive GC patients. In HER2-postive GC, the dysregulation of PI3K/AKT and MAPK/ERK signaling pathways has been reported, and inhibition of these pathways is an important therapeutic strategy. MiR-143 is known to act as a tumor suppressor in several cancers, such as bladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…From the previous studies, miR-143 functioned as tumor suppressor miRNA in several malignancies through targeting KRAS and its effector molecules [10][11][12]. To explore the suppressive role of miR-143 associated with KRAS signaling pathways in breast cancer cells, we examined the expression levels of KRAS by western blot analysis and qRT-PCR.…”
Section: Overexpression Of Mir-143 Inhibited Cell Growth Of Mb-231 Anmentioning
confidence: 99%
See 3 more Smart Citations
“…From the previous studies, miR-143 functioned as tumor suppressor miRNA in several malignancies through targeting KRAS and its effector molecules [10][11][12]. To explore the suppressive role of miR-143 associated with KRAS signaling pathways in breast cancer cells, we examined the expression levels of KRAS by western blot analysis and qRT-PCR.…”
Section: Overexpression Of Mir-143 Inhibited Cell Growth Of Mb-231 Anmentioning
confidence: 99%
“…Western blot analysis was performed as described in previous reports [10,11]. The following antibodies were used in this study.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we found that the expression level of MIR143‐3p is also downregulated in HER2‐positive GC cells and that ectopic expression of MIR143 induced cell growth suppression in those cells 52 . In that same study we demonstrated that MIR143‐3p targets KRAS effector signaling genes such as KRAS, AKT and ERK, leading to suppression of GC cell growth, and clarified that MIR143‐3p indirectly silences human epidermal growth factor receptor 2 (HER2), resulting in suppression of KRAS activation and its effector signaling pathways 52 …”
Section: The Role Of Mir143‐3p On Rat Sarcoma Signaling Network In Vmentioning
confidence: 99%